2016
DOI: 10.1111/acel.12546
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfide protects against oxidative stress and extends lifespan via a methionine sulfoxide reductase A-dependent catalytic mechanism

Abstract: SummaryMethionine (Met) sulfoxide reductase A (MsrA) is a key endogenous antioxidative enzyme with longevity benefits in animals. Only very few approaches have been reported to enhance MsrA function. Recent reports have indicated that the antioxidant capability of MsrA may involve a Met oxidase activity that facilities the reaction of Met with reactive oxygen species (ROS). Herein, we used a homology modeling approach to search the substrates for the oxidase activity of MsrA. We found that dimethyl sulfide (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…Expression of fRMSR enzymes lost during evolution can lead to an increased lifespan in animals [ 77 ]. Likewise, expression of MSRA, together with DMSO, can also extend an organism’s life [ 78 , 79 ]. Thus, archaeal MSR enzymes, including those yet to be discovered, may hold a key to the fountain of youth.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Expression of fRMSR enzymes lost during evolution can lead to an increased lifespan in animals [ 77 ]. Likewise, expression of MSRA, together with DMSO, can also extend an organism’s life [ 78 , 79 ]. Thus, archaeal MSR enzymes, including those yet to be discovered, may hold a key to the fountain of youth.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recent bioinformatics and high throughput experimental screening approaches lead to the identification of candidate CR/DR mimetics in C. elegans that now require investigation in higher organisms (Calvert et al, 2016; Lucanic et al, 2016). Additional compounds that recently were shown to increase wildtype C. elegans lifespan in candidate testing or small scale screening approaches include small molecules and metabolites such as dimethyl sulfide (Guan et al, 2017), α-ketoacids (Mishur et al, 2016), fructose (Zheng et al, 2017), the d-fructose epimer d-allulose (Shintani et al, 2017), the ω−3 polyunsaturated fatty acid alpha-linolenic acid (ALA) and ALA-derived oxylipin-metabolites (Qi et al, 2017), the proteasome activator 18α-Glycyrrhetinic Acid, a triterpenoid from licorice (Papaevgeniou et al, 2016) and FDA-approved drugs such as rifampicin for tuberculosis (Golegaonkar et al, 2015) and the angiotensin-converting enzyme inhibitor captopril (Kumar et al, 2016) and hydralazine, which are both used to treat hypertension (Dehghan et al, 2017). Many of these compounds apparently act, at least in part, by activating or stabilizing lifespan-regulatory key transcription factors (Table 1), such as daf-16 (18α-Glycyrrhetinic Acid, rifampicin, captopril), hlh-30 (selective inhibitors of nuclear export), hif-1 (α-ketoacids), nhr-49 (ALA) and skn-1 (ALA-metabolites, 18 α-Glycyrrhetinic, hydralazine).…”
Section: Pharmacologic Lifespan Extensionmentioning
confidence: 99%
“…EPR was performed as described in our previous reports with some modifications [28,29] . DMPO was used as a free radical trapper.…”
Section: Electron Paramagnetic Resonance (Epr)mentioning
confidence: 99%
“…MsrA has historically been considered a reductase, not an ROS scavenger, for the reaction of Met with oxidizing species was widely viewed as a natural process. Recent studies from our lab have indicated that the antioxidant capability of MsrA may involve a Met oxidase activity that facilities the reaction of Met with ROS, which may underlie the effect of MsrA on neuroinflammation and lifespan [28,29] .…”
mentioning
confidence: 99%
See 1 more Smart Citation